Modernization of the State Department: Changes from FDR to Dean Acheson 1945-1953 - Schwan, Kyle (My University, 2016)
This capstone looks at and analyzes the changes in organization and administration of the United States Department of State from the middle of the 1940s through 1953. Looking at the organization of the State Department during these years will show the influence World War II had on the Department as well as how the Department grew in order to manage all of the new areas of interest of the United States Government. It also looks at the role that each Secretary of State played in making changes to the State Department, especially the decisions and actions taken by Dean Acheson. Official State Department documents along with Congressional records are used, as well as the personal accounts of various people including Dean Acheson.
Keywords: World War II--United States; Acheson, Dean, 1893-1971; Department of State Building (Washington, D.C. : 1930-1949)